2011
DOI: 10.1021/jo201966g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Nonsymmetric Cyclopentene-Based Dithienylethenes

Abstract: Nonsymmetric cyclopentene-based dithienylethenes, containing both thienyl and benzothienyl units, have been synthesized for the first time, employing intramolecular McMurry reaction as a key transformation to target compounds 10 and 16. Photochromic properties of these compounds were examined in toluene and acetonitrile solutions, PMMA layers, solid films, and crystal phase. To explain an unprecedented single-crystalline photochromism phenomena of 10, X-ray crystallographic analysis was performed, revealing a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…Previously, we showed that the halide insertion into nonsymmetric dithienylethenes did not crucially influence the absorption spectra of the compounds. 23 In turn, symmetric photochromes fully confirmed this observation displaying basically no distinction in the absorption spectra: both the wavelengths of absorption band maxima for cyclic forms and values of absorption density for either unsubstituted or halidesubstituted compounds looked analogous, showing no dependence of these parameters on the halide origin.…”
Section: Spectral and Kinetic Characteristicsmentioning
confidence: 61%
See 3 more Smart Citations
“…Previously, we showed that the halide insertion into nonsymmetric dithienylethenes did not crucially influence the absorption spectra of the compounds. 23 In turn, symmetric photochromes fully confirmed this observation displaying basically no distinction in the absorption spectra: both the wavelengths of absorption band maxima for cyclic forms and values of absorption density for either unsubstituted or halidesubstituted compounds looked analogous, showing no dependence of these parameters on the halide origin.…”
Section: Spectral and Kinetic Characteristicsmentioning
confidence: 61%
“…23 Besides, as was shown, bromides in dithienylethenes remained intact under McMurry conditions. Acylation of benzothiophene 7 with glutaryl dichloride was rather straightforward and afforded diketone 8, which was subsequently converted to the target dibromide 6 by McMurry reaction in excellent overall yield.…”
Section: Synthesismentioning
confidence: 72%
See 2 more Smart Citations
“…2,21-24 Another approach involves the Pd-catalyzed cross-coupling of 1,2dibromocyclopentene (pathway II in Scheme 1). 4, 11,12,25,26 These methods are quite suitable for thiophene and benzothiophene derivatives, including unsymmetric, 23 but they are generally limited to azole compounds (oxazole, imidazole, thiazole) because the starting compounds are difficult to access and the reaction requires harsh conditions. In addition, an alternative synthesis was used for the preparation of diarylcyclopentene derivatives by the reduction of the carbonyl group in diarylcyclopentenones.…”
Section: -4mentioning
confidence: 99%